Analysis of Basic and Potential Economic Sectors in Tana Tidung Regency - Ramdani, Aulia; Sonu, Karolus; Alexiana, Cancy; Kurniawan (Journal of Regional Economics and Development, 2026)
This study aims to analyze the basic and potential economic sectors that can drive economic growth in Tana Tidung Regency. This research is useful in providing a significant boost in the form of appropriate programs and policies to encourage economic growth in Tana Tidung Regency. Investors can also identify investment opportunities in potential sectors. This study uses data from the Central Statistics Agency (BPS) of Tana Tidung Regency and North Kalimantan Province for 2022-2024. The data analysis technique used is the Location Quotient (LQ) to identify the basic sectors and the Klassen Typology to identify potential sectors in Tana Tidung Regency. The results of the data analysis indicate that the basic sectors in Tanah Tidung Regency are agriculture, forestry, and fisheries, as well as mining and quarrying. Investors have investment opportunities in several potential sectors. The results of the data analysis indicate that potential sectors in Tanah Tidung Regency are the manufacturing industry, construction, wholesale and retail trade, car and motorcycle repair, financial services and insurance, real estate, and corporate services.